1857 : The Real Story of the Great Uprising - Vishnu Bhatt (New Dehli, India HarperCollins India, 2011)
Around the middle of the nineteenth century, when the East India Company had consolidated its hold over the Indian subcontinent, a Chitpavan Brahmin by the name of Vishnu Bhatt GodsheVersaikar decided to cross the Vindhya mountains with his aged uncle to earn some money. What he had not foreseen was how his trip would coincide with the historic Sepoy Mutiny and play havoc with their travel plans. This is a unique first-person, eyewitness account of their picaresque journey, recorded several years after their return home. This is also perhaps the only documentation of a momentous event in the history of India by an impoverished but learned young beggar-priest. In this gripping yet sensitive translation, Mrinal Pande brings to life for today's reader the account of Vishnu Bhatt's adventures, and the fascinating history of its publication.
Keywords: Biographies / Memoirs -- Biographies / Memoirs